When Translation Competence Is Not Enough: A Focus Group Study of Medical Translators - Nisbeth Brøgger, Matilde (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2017)
Functionalist approaches to translation brought about a shift in the status and role of the translator: the translator is now considered to be an active, responsible agent in the communication process, which increases the importance of translation expertise and translation competence. Translation competence has thus attracted mounting research interest; however, empirical studies have primarily been conducted in controlled environments, omitting the translation context that professional translators usually work within. This study offers empirical evidence of the importance of the translation context when investigating translation competence. Based on a previous empirical study of translated Patient Information Leaflets, which showed a lack of translation competence, this study includes the translators’ perception using the focus group methodology. Results show the strong influence of contextual constraints on medical translators’ processes and thus products. The study concludes that an analysis of translation products alone may give a skewed picture of translators’ competence.